STRATEGI PENGELOLAAN KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) UNIT V (Wilayah Kabupaten Minahasa, Kota Tomohon, Kabupaten Minahasa Tenggara Dan Kabupaten Minahasa Selatan) - Deiby Elsa Gisisi; Hengki Djemie Walangitan; Zetly Estevanus Tamod (Sam Ratulangi University, 2019)
The research aims to (1) Analyze management strategies to create productive and sustainable forests, (2) Determine priority strategies in managing Unit V Production Forest Management (KPHP) Units. The research is conducted from August to September 2017 in the Production Forest Management Unit (KPHP) Unit V in 4 (four) districts / cities namely Minahasa Regency, Tomohon City and Southeast Minahasa Regency and South Minahasa Regency. Data collection methods in this study include primary data and secondary data, primary data includes: 1) Strategic environmental issues through FGD forums, 2) Strategic priority determination through expert opinion, Secondary data obtained by studying the relevant data: 1) The Unit V / KPHP forest governance document in the regency / city area, namely Minahasa Regency, Tomohon City, Southeast Minahasa Regency and South Minahasa Regency, 2) Biophysical, socio-economic and institutional data of the study area obtained from Unit V RPHJP document data. Analysis tools are descriptive analysis, and a combination of Analytical Hierarchy Process (AHP) and SWOT. The results of the study show that (1) the management strategies used in Unit V KPHP are aggressive strategies or support policies established in KPHP unit V management. (2) priority strategy in KPHP management Unit V is managing the area, utilizing watershed rehabilitation and strengthening institutional and safeguarding Unit V's core KPHP areas in forest management, as well as the development of forest utilization models, market-oriented agroforestry, and adequate financial support in Unit V KPHP operations.*eprm*